Do You Know My Name? Learning Mandarin through Game-based Learning - Khaw, Hong Yi; Lim, Phei Chin; Suriati Khartini, Jali (2023)
Mandarin is difficult for a couple of reasons, such as the complexity of writing system, Chinese characters, and tone. It can be excruciatingly hard to learn Mandarin without motivation and immediate positive feedback. With the growth of technology, games now play an essential role in language learning. Games enable learners to actively participate in activities, and to strengthen their affective reactions such as interest and motivation. There are various language learning games available on the market but most of them are using similar ways such as flashcards which is very repetitive. A firstperson view gameplay will be developed in this project to explore the possibility of immersive game-based learning and to provide an entertaining learning environment that motivates learners. The knowledge of vocabulary words for three topics which are numbers, colours, and direction are covered. Players are recruited to participate in our experiments. A paired sample t-test, t (14) = 27.4, p < .001 showed that there is improvement in the Mandarin learning achievement of players before and after playing the game. The average mean value of 4.55 is achieved using the RIMMS survey showed promising result in perceived motivation of the tested gameplay.